Electronically Controlled Impedance Tuner for 5.8 GHz Band - Piotr Wilkon; Kamil Staszek (IEEE Access)
In this paper, a single-port impedance tuning network is proposed. The presented circuit allows for electronic programming of the reflection coefficient over a broad range, covering the entire unit circle, making the network well-suited as a reference impedance in sensing systems. The system operates exclusively by applying appropriate attenuation values through electronically programmable attenuators, rather than utilizing variable phase shifters, which are inherently narrowband and introduce high insertion losses. The tuning process consists of dividing the input signal among three separate paths with different phase shifts, applying attenuation to each path, combining the signals, and returning them to the transmitter, thereby mimicking reflection. The proposed network consists of a microwave PCB and standard electronic components, making it easily repeatable and inexpensive to fabricate. Moreover, the circuit can be easily extended for wideband operation by employing wideband directional couplers and fixed phase shifters. A detailed description of the system, including theoretical analysis and corresponding design equations, is provided. The performance of the fabricated network was verified by measuring the effective reflection coefficients for all attenuation settings at 5.8 GHz, yielding magnitude coverage from -30 dB to higher than 0 dB at any phase angle. The obtained results demonstrate an excellent tuning range and strong agreement with theoretical predictions.